Merapi Volcano Eruptions 2006 - Subandriyo, . (2007)
The last Merapi volcano eruption in 26 April 2006 begun since lava dome was formed and the peak occurred in 14 June 2006 when the hot avalance could reach 7 km towards Kali Gendol (Gendol river). Merapi eruption 2006 direction has changed from South West (since 1961) to South East (i.e. Kali Gendol). The objectives of this paper were to describe the changes of hazard status of the Southern-South eastern Merapi volcano due to the 26th April 2006; (2) to evaluate the risk of some populated areas in the Southern-South eastern Merapi volcano; (3) to formulate the recommendation for settlement improvement as well as the master plan in the stu.dy area. Thmethod applied to achieved the objectives were including the satellite imageries interpretation, new topographic map interpretation, current landuse status evaluation, and field check. The data were evaluated and analyzed descriptively based on the spatial arrangement of hazard - risk status and settlement area. This changes affect the potential hazard at South - South East district covered Kali Gendol, Kali Kuning, and Kali Boyong. The villages are only 4 km distance from the eruption center, and the higher population factor would increase the risk. To minimise the ri sk of volcanic hazard in future, it is really needed to rearrange the master plan at South - South East district